AB0684 Comparison of Two Referral Strategies for the Diagnosis of Axial Spondyloarthritis in Romania: the Rabbit Study. (10th June 2014) - Ancuta, C.M.; Pomirleanu, C.; Opris, D.; Chirieac, R.; Codreanu, C.; Bojinca, M.; Rednic, S.; Ionescu, R.
Abstract : Background: Despite recent advances in classifying and diagnosing axial spondyloarthropathies (SpA), screening of patients with chronic low back pain and referral from the primary care settings remain unsatisfactory. Objectives: RADAR study aimed to identify the best referral strategy for diagnosing axial SpA in patients with chronic back pain (CBP). Methods: Hundred-and-six Romanian patients with CBP occurring before 45 years were assigned to either a simple (any of inflammatory back pain, HLA-B27 positivity or sacroiliitis on imaging) (38 patients) or a complex referral strategy (two of inflammatory back pain, HLA-B27, sacroiliitis, familial SpA history, extra-articular manifestations, good response to nonsteroidal antiinflammatory drugs) (68 patients). Primary end points were to compare the percentage of patients diagnosed with definite axial SpA by referral strategy and the degree of concordance of selection criteria between referring physicians and rheumatologists. Results: Final analysis was performed in hundred-and-three patients (37 per strategy 1, 66 per strategy 2); definite axial SpA was established in 70.3% and 65.2% patients by referral strategies, mostly in the radiographic disease (56.8% and 54.5%). The first three commonly used for referral were inflammatory back pain (99.1%) with 83.2% concordance rate with rheumatologists, 89% positive predictive value, 94.2% sensitivity, 57.9% specificity; response to NSAIDs (50.9%) with 90.4% concordance rate, 79.7% positive predictive value, 80.9% sensitivity, 26.3% specificity; and sacroiliitis (48.1%), 72.9% concordance rate, 75% sensitivity Conclusions: Both referral strategies showed comparable effectiveness in diagnosing patients with axial SpA; a simple screening strategy using three criteria should be routinely used in primary care settings in recognizing axial SpA. Acknowledgements: This study was supported by a grant from Schering-Plough (presently Merck & Co Inc, Whitehouse Station, New Jersey, USA). Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5577